Acute and subchronic toxicity as well as evaluation of safety pharmacology of modified pulsatilla granules - Rui-lin JIA; Xu SONG; Yu-fei GUO; Zhong-qiong YIN; Fei LIU; Juan XIONG; Qiu-yan LIU; Ren-yong JIA; Li-xia LI; Yuan-feng ZOU; Li-zi YIN; Chang-liang HE; et al. (Journal of Integrative Agriculture, 2017)
The present study investigated acute and subchronic toxicity and safety pharmacology of modified pulsatilla granules (MPG) to provide a basis for a comprehensive understanding of MPG toxicity. The results of acute toxicity testing showed that the median lethal dose of MPG was more than 5000 mg kg−1, suggesting that MPG was considered as practically non-toxic. The subchronic toxicity study for 30 days was conducted by daily oral administration at doses of 375, 750 and 1 500 mg kg−1 in Sprague-Dawley rats. The results of subchronic toxicity study showed that the body weight and relative organ weight were not significantly changed by administration of MPG. The clinical chemistry study showed that MPG could induce kidney and liver damages. In histopathological, mild lesions in liver and kidney were also observed, suggesting that the liver and kidney might be potential target organs of MPG. In the safety pharmacology study, MPG did not exhibited any side effects to rats in cardiovascular system, respiratory system and central nervous system. These results suggested that MPG could be considered safe for veterinary use.